Ultrasonic Assisted Extraction of Jatropha Seed Oil and Analysis of Oil Component by HPLC - Zhang, Hailing; Liu, Shuyu (Asian Journal of Chemistry, 2014)
Ultrasonic extraction technique was applied for the extraction of oil from Jatropha seeds.The optimum conditions for the lab scale ultrasonic extraction were obtained at 30 °C, ultrasonic extraction time of 4 min, ratio of liquid to solid of 14:1(mL/g) and ligarine (90-120 °C) as a solvent. Under the optical conditions, the yield of oil was 42.52%. The main components of jatropha seed oil were analyzed by the HPLC method.